Magnetic Resonance Imaging Characteristics of Primary Intraspinal Peripheral Primitive Neuroectodermal Tumour. Issue 3 (August 2013) - Wu, Guangyao; Ghimire, Prasanna; Zhu, Ling; Baral, Aparajita; Su, Jiajia
Purpose: The purpose of our study was to describe the salient magnetic resonance imaging (MRI) findings in primary intraspinal peripheral primitive neuroectodermal tumour (PNET). Methods: A retrospective review of the clinical and MRI images of 7 pathologically proven cases of intraspinal peripheral PNETs was performed. The various parameters, such as vertebral level of involvement; tumour location, size, focality, and margin; signal intensity of the lesion; the presence of hemorrhage or calcification; any signal voids; assessment of the adjacent cord for cord compression; cord dilatation; the presence of paraspinal tissue mass; or vertebral or other bony changes, were analysed. Results: All 7 patients had lesions in the thoracolumbar region. Three patients had extradural lesions, 4 had intradural extramedullary lesions, and none had intramedullary lesions. Six lesions were well circumscribed. Only 1 patient had multifocal involvement. All lesions were of hypointense or isointense signal on T1-weighted imaging, whereas all but one were hyperintense on T2-weighted imaging. Lesions enhanced heterogeneously except 1 intradural extramedullary lesion, which enhanced homogeneously. A paraspinal mass was noticed in 2 patients. Vertebral collapse was present in 1 patients. Conclusion: Intraspinal peripheral PNETs are rare spinal tumours. Although imaging characteristics are not specific, a focal circumscribed lesion in a young individual at the intramedullary, extramedullary intradural, or extradural spinal location that shows hypointense and hyperintense signal on T1- and T2-weighted images, respectively, requires PNET to be considered in the differentials.